Historical and contemporary studies of Wrocław’s climate – measurements and models - Szymanowski, Mariusz; Drzeniecka-Osiadacz, Anetta; Sawiński, Tymoteusz; Kryza, Maciej (Acta Geographica Lodziensia, 2019)
In this paper, we present the history and development of urban climate research in Wrocław, undertaken at the University of Wrocław (UWr), mainly at the Department of Climatology and Atmosphere Protection (DCAP). The main scientific topics, such as mesoclimate, bioclimate, urban heat island, and air quality in Wrocław are described. There were two milestones in urban climate research at UWr. First, the turn of the 21st century was associated with the introduction of automatic weather stations, mobile measurements and acoustic soundings, supported with GIS analysis, for the spatio-temporal studies of Wrocław (bio)climate. In the second decade of the 21st century, our research is mostly related to urban air quality. New measuring techniques have been introduced, supported with numerical models (WRF, WRF-Chem), and much greater attention has been devoted to scientific research applications (the LIFE-APIS/PL project).